Association of Maternal Report of Infant and Toddler Gastrointestinal Symptoms With Autism: Evidence From a Prospective Birth Cohort - Bresnahan, Michaeline (JAMA Psychiatry, 2015)
IMPORTANCE: Gastrointestinal (GI) comorbidities are frequently described in association with autism spectrum disorder (ASD). However, the prevalence of GI disturbances and the age at which such problems first appear are unclear, and their specificity for ASD compared with other neurodevelopmental disorders is uncertain. OBJECTIVE: To compare maternal report of GI symptoms during the first 3 years of life in children with ASD, developmental delay (DD), and typical development (TD). DESIGN, SETTING, AND PARTICIPANTS: This large prospective cohort study consists of participants in the Norwegian Mother and Child Cohort Study. During a 10-year period (January 1, 1999, through December 31, 2008), women throughout Norway were recruited at the first prenatal ultrasonographic visit (approximately 18 weeks’ gestation). The study enrolled 95 278 mothers, 75 248 fathers, and 114 516 children. Our analyses are based on MoBa data released through October 1, 2013, and NPR diagnoses registered through December 31, 2012, and include children born from January 1, 2002, through December 31, 2008, with completed age 18- and 36-month questionnaires. EXPOSURES: We defined 3 groups of children: children with ASD (n = 195), children with DD and delayed language and/or motor development (n = 4636), and children with TD (n = 40 295). MAIN OUTCOMES AND MEASURES: The GI symptoms were based on maternal report of constipation, diarrhea, and food allergy/intolerance. RESULTS: Children with ASD were at significantly increased odds of maternally reported constipation (adjusted odds ratio [aOR], 2.7; 95% CI, 1.9–3.8; P < .001) and food allergy/intolerance (aOR, 1.7; 95% CI, 1.1–2.6; P = .01) in the 6- to 18-month-old age period and diarrhea (aOR, 2.3; 95% CI, 1.5–3.6; P < .001), constipation (aOR, 1.6; 95% CI, 1.2–2.3; P < .01), and food allergy/intolerance (aOR, 2.0; 95% CI, 1.3–3.1; P < .01) in the 18- to 36-month-old age period compared with children with TD. Similar results for these symptom categories were observed in comparisons with children with DD, but ORs were slightly lower. Mothers of children with ASD were significantly more likely to report 1 or more GI symptom in either the 6- to 18-month or the 18- to 36-month-old age period and more than twice as likely to report at least 1 GI symptom in both age periods compared with mothers of children with TD or DD. CONCLUSIONS AND RELEVANCE: In this large prospective cohort, maternally reported GI symptoms are more common and more often persistent during the first 3 years of life in children with ASD than in children with TD or DD.